2020
DOI: 10.21608/jappmu.2020.106503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Condition Score at Calving on Ovarain Activity and Subsequent Reproductive Characteristics during Postpartum Period in Crossbred Cows تأثیر حالة الجسم عند الولادة على النشاط المبیضى والخصائص التناسلیة اثناء فترة مابعد الولادة فى الأبقار الخلیطة

Abstract: The present investigation aims to determine the effect of body condition score (BCS) at calving on ovarian activity and subsequent reproductive characteristics during postpartum period in crossbred cows. Thirty-six crossbred cows (Baladi cows x Friesian cows) week post-calving were used and divided into three groups of 12 cows for each group (BCS: less than 3 equal to 3 and more than 3) according to BCS. The results demonstrated that, uterine involution period, first ovulation and estrous was significantly lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…In contrast, regardless of yield, cows with low BCS exhibited poor fertility (Berry et al, 2003). Damarany (2020) showed that the interval between calving and first service in crossbred cows with BCS <3 was significantly longer (P<0.05) than cows with higher BCS. Low BCS as a consequence of selection for high yield may alter the level of circulating gonadotrophins influencing calving to service interval and subsequent fertility .…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, regardless of yield, cows with low BCS exhibited poor fertility (Berry et al, 2003). Damarany (2020) showed that the interval between calving and first service in crossbred cows with BCS <3 was significantly longer (P<0.05) than cows with higher BCS. Low BCS as a consequence of selection for high yield may alter the level of circulating gonadotrophins influencing calving to service interval and subsequent fertility .…”
Section: Resultsmentioning
confidence: 98%